1999
DOI: 10.1557/jmr.1999.0445
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of Zr57Nb5Al10Cu15.4Ni12.6 metallic glass matrix particulate composites

Abstract: To increase the toughness of a metallic glass with the nominal composition Zr 57 Nb 5 Al 10 Cu 15.4 Ni 12.6 , it was used as the matrix in particulate composites reinforced with W, WC, Ta, and SiC. The composites were tested in compression and tension experiments. Compressive strain to failure increased by more than 300% compared with the unreinforced Zr 57 Nb 5 Al 10 Cu 15.4 Ni 12.6 , and energy to break of the tensile samples increased by more than 50%. The increase in toughness came from the particles restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
93
1

Year Published

2002
2002
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(100 citation statements)
references
References 18 publications
(21 reference statements)
3
93
1
Order By: Relevance
“…2,6 However, the final fracture of BMGs occurs catastrophically and involves very little overall plastic deformation due to highly localized shear banding. 6 To overcome the problem of limited plasticity in BMGs, several composite materials have been developed, [7][8][9][10][11][12][13][14][15][16][17] which can be broadly classified in two groups according to their processing: (i) ex situ and (ii) in situ formed composites. Several trials have previously been made to improve the ductility by introducing quasicrystalline 18,19 or nanocrystalline 20,21 precipitates in a glassy matrix upon partial crystallization during annealing treatment of the amorphous precursors.…”
Section: Introductionmentioning
confidence: 99%
“…2,6 However, the final fracture of BMGs occurs catastrophically and involves very little overall plastic deformation due to highly localized shear banding. 6 To overcome the problem of limited plasticity in BMGs, several composite materials have been developed, [7][8][9][10][11][12][13][14][15][16][17] which can be broadly classified in two groups according to their processing: (i) ex situ and (ii) in situ formed composites. Several trials have previously been made to improve the ductility by introducing quasicrystalline 18,19 or nanocrystalline 20,21 precipitates in a glassy matrix upon partial crystallization during annealing treatment of the amorphous precursors.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Fig. 4 and 19) have reported that particulates of W, WC, Ta or SiC can restrict the propagation of shear bands and promote the generation of multiple shear bands. In the present study, the existence of the ZrO 2 particulates, on the one hand, makes shear band propagation more difficult, which leads to an increase of compressive strength.…”
Section: Discussionmentioning
confidence: 94%
“…The Young's modulus of the foam was 3.1 GPa. Elastic strain, compressive fracture strength, and Young's modulus of the bulk amorphous alloy are, respectively, 2%, 1800 MPa, and 84.7 GPa [5]. The poor mechanical response of the foam may be attributed to its crystallinity and to defects in the structure, the latter having an exaggerated effect due to the high ratio of pellet/pore size to sample diameter [8].…”
Section: Discontinuous Refractory Patterns (Pellet Infiltration Technmentioning
confidence: 99%
“…However when loaded beyond the elastic limit, glass-forming alloys are prone to catastrophic shear localization and failure without significant ductility (often <1%), making them unreliable for critical structural applications. One method of avoiding this problem has been to introduce additional phases such as ceramics, ductile metals, or native crystalline phases into the amorphous alloy [3][4][5][6][7]. Although a marked improvement in fracture strain can be achieved in such composites, the choice of reinforcement is limited by issues of reaction/dissolution and heterogeneously nucleated crystallization at the matrix/reinforcement interface, resulting in a density that is often significantly higher than that of the monolithic glass.…”
Section: Introductionmentioning
confidence: 99%